The Impact of Implementation of The Community Activity Restrictions Policy on The Reaction of The Capital Market in Indonesia Especially in LQ45 Companies - Kufanda, Muhammad Royhan; Intriani, Bila Eprilita (International Journal of Social Science and Business, 2022)
Events/announcements of the implementation of the Policy for the Enforcement of Community Activity RestrictionsÂ  that occurred due to Covid-19 had an impact on stock price fluctuations. This study aims to prove whether there are differences before an event occurs (event studies) that have an impact on various fields and the surrounding environment. The event referred to in this study is Covid-19, especially when the Indonesian Government issued the PPKM policy for the first time in Indonesia. This condition certainly has an impact on all sectors including stock trading on the Indonesia Stock Exchange. By using a sample of 30 companies in LQ45 with a safe research period focusing on the day before (-5 to -1) and the day after (+1 to +5) the announcement of the PPKM policy. From the results of the research conducted with the Paired Sample t-test, the results showed that there was no significant difference before and after the implementation of the Policy for the Enforcement of Community Activity Restrictions (PPKM). So it can be said that the implementation of Community Activity Restrictions (PPKM) has no impact on the average abnormal return obtained by investors and the average trading volume activity during the event period (H-5 to H+5) the implementation of the Policy for the Enforcement of Community Activity Restrictions (PPKM).